The comparative analysis of political programs: large-N Analyses with data from international organizations - Anja P. Jakobi (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2007)
This paper deals with the methodological question of using data from international organizations (IOs) for comparative analysis. It explores how large-N analyses can profit from using different types of data, including text analysis. The paper proceeds as follows: First, it is introduced for which types of research question certain types of IO data might be accurate. Then, data collection of different IOs is presented, distinguishing verbal and statistical data. In a third step, it is shown how extent and origin of international agenda setting processes can be assessed methodologically, using the data described before. Finally, shortcuts of such a mixed-method procedure are sketched. The paper is based on an example of education policy but transfers to other policy fields are easily possible. – – Das Arbeitspapier beschäftigt sich mit methodischen Fragen in der vergleichenden Politikwissenschaft, im speziellen mit der Nutzung von Daten internationaler Organisationen (IOs) für 'large-N'-Analysen. Dabei geht der Artikel wie folgt vor: Zunächst wird vorgestellt, für welche Typen von Forschungsfragen bestimmte Arten von IO-Daten besonders geeignet sind. Dann werden unterschiedliche Daten internationaler Organisationen vorgestellt, wobei zwischen verbalen und statischen Daten unterschieden wird. In einem dritten Schritt wird gezeigt, wie eine Kombination der verschiedenen Datentypen genutzt werden kann, um internationale Agenda Setting Prozesse empirisch zu untersuchen. Schließlich werden Fallstricke dieses Verfahrens präsentiert und abschliessend der Nutzen des Verfahrens skizziert. Der Artikel nutzt ein Beispiel aus dem Politikfeld Bildung, Übertragungen auf andere Politikfelder sind jedoch leicht möglich.
Keywords: 330